Sistem Pendukung Stres Kerja Terhadap Tingkat Turnover Intention dengan Multi Attribute Utility Theory - Muhammad Muhsin Kamal (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
The level of employee turnover intention at PT. Prima Karya Sarana Sejahtera (PKSS) Jakarta 1 branch in the last 4 years has reached 1.675 employees. Turnover intention is the tendency or intention of employees to voluntarily stop working or move from one workplace to another. PT PKSS itself is a company engaged in outsourcing. Outsourcing is the use of labor services recruited to fill certain positions in the client/user company of PT PKSS. Decision support systems are information systems or data presentation, modeling and data manipulation to support decision making in an organization or company. In supporting decision making using the Multi Attribute Utility Theory (MAUT) method so that it can see or assess the level of work stres of outsourced or outsourced employees and will make decisions more quickly to provide direction, motivation, and guidance to employees to increase employee work productivity. Keywords—Decision Support System; Multi Attribute Utility Theory (MAUT); Work Stres.